2003
DOI: 10.2113/49.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous index nannofossils (coccoliths) of the lowermost Paleocene originated in the late Maastrichtian

Abstract: ABSTRACT:The calcareous nannofossil species Neobiscutum romeinii, N. parvulum, and Cruciplacolithus primus, are considered in modern zonation schemes as index species for the lowermost Paleocene. Our studies, however, reveal that they are consistently present in upper Maastrichtian calcareous nannofossil zone CC26. The two Neobiscutum species were found several meters below the Cretaceous-Paleogene (K-P) boundary in cores from Brazos River (Texas) and Antioch Church (Alabama), and in outcrops at Geulhemmerberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Geobios 43 (2010) [569][570][571][572][573][574][575][576][577][578][579] Due to their very small size, calcareous nannofossils are comparatively easily resedimented and reworked. This fact has been brought forth in several papers on the K-Pg boundary, showing Cretaceous taxa in Danian samples and vice versa; but only occasionally has the incidence of the activity of tracemakers on calcareous nannofossils redistribution been considered, and in almost all cases this aspect has been alluded to in general terms (e.g., Thierstein and Okada, 1979;Thierstein, 1981;Smit and Romein, 1985;Henriksson, 1996;Pospichal, 1996;Romein et al, 1996;Mai et al, 2003;Bown, 2005;Lamolda et al, 2005). Thus, the role of tracemakers in the reworking of microfossils is usually underestimated.…”
Section: Introductionmentioning
confidence: 97%
“…Geobios 43 (2010) [569][570][571][572][573][574][575][576][577][578][579] Due to their very small size, calcareous nannofossils are comparatively easily resedimented and reworked. This fact has been brought forth in several papers on the K-Pg boundary, showing Cretaceous taxa in Danian samples and vice versa; but only occasionally has the incidence of the activity of tracemakers on calcareous nannofossils redistribution been considered, and in almost all cases this aspect has been alluded to in general terms (e.g., Thierstein and Okada, 1979;Thierstein, 1981;Smit and Romein, 1985;Henriksson, 1996;Pospichal, 1996;Romein et al, 1996;Mai et al, 2003;Bown, 2005;Lamolda et al, 2005). Thus, the role of tracemakers in the reworking of microfossils is usually underestimated.…”
Section: Introductionmentioning
confidence: 97%
“…Instead, the first occurrence of Biantholithus sparsus should be used as the certain age marker as is proposed in the zonation scheme by Varol (1998). Generally, this species is considered as rarely found (Mai et al 2003;Molina et al 2006), however, it was also noted in the Carpathians (Oszczypko et al 1995;Bubík et al 1999;Summesberger et al 1999). On the other hand, van Heck & Prins (1987) and Švábenická (2001) claimed the occurrence of B. sparsus even in the Upper Maastrichtian.…”
Section: Calcareous Nannofossil Biostratigraphymentioning
confidence: 95%
“…The calcareous nannofossil biostratigraphy of the K/Pg boundary is handicapped by the problem of the reworked assemblages (Bown 2005;Kędzierski et al 2011 and references cited therein) and growing evidence of some taxa such as Cruciplacolithus primus, which were previously considered as newcomers, but now as Late Maastrichtian in origin (Mai et al 2003). Similarly, the Lower Paleocene foraminiferid assemblages also comprise reworked and survivor taxa (Huber 1996;Gallala et al 2009;Slimani & Toufiq 2013).…”
Section: Remarks On K/pg Boundary Biostratigraphy Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that it also occurs in shelf sediments of Late Maastrichtian age and so should be considered a survivor species (Mai et al, 2003). Like Cyclagelosphaera it has often been regarded as an extinct genus but one species C. neohelis occurs sporadically in coastal-neritic environments (e.g.…”
Section: -5 Floristic Studiesmentioning
confidence: 99%